DESAIN KORIDOR VEGETASI UNTUK MENDUKUNG NILAI KONSERVASI DI KAWASAN PERKEBUNAN KELAPA SAWIT - Danang Wahyu Purnomo (Environmental Research Center (PPLH) of Udayana University, 2012)
Habitat fragmentation causes genetic isolation that would reduce biodiversity in the forest. PT Swakarsa Group has a 12 blocks of conservation area which are separated by the palm oil plantations. Each of conservation has a variety of environmental characteristics. Strategies to cope the impact of habitat fragmentation on this plantation are habitat corridors development. This study aims to design of vegetation corridors to support the conservation value in the palm ??oil plantations. Vegetations were observed by nested sampling system, plot 20mx20m (for trees) and 2mx2m plot (shrubs) were placed along transects. Conservation value was measured based on the conservation status of bird species and frequency of attendance. Bird assemblages were estimated by point counts. Corridor design was determined based on the USDA NRCS, while the vegetation compositions were determined under the provisions of MacGowan. There were two types of corridors that can be applied in the plantation areas; remnant corridors and introduction corridors. There were two main locations that need to be created corridors to enhance biodiversity conservation in the PT Swakarsa Group. Block VI and Block VIII were the core conservation area where contained more genetic resources need to be linked to other blocks. Remnant corridors could be built in the area along the river and banks of ponds. While introduction corridors were recommended to place on the edge of the road.